Die Hochschullandschaft im demographischen Wandel – Entwicklungstrends und Handlungsalternativen - Michael Fritsch; Matthias Piontek (Raumforschung und Raumordnung, 2015)
What are the effects of the expected demographic development for universities? Our analysis shows that the expected demographic change will affect regions and universities quite differently according to their location, status, and size. A decreasing number of students could particularly endanger the existence of small universities of applied sciences in regions with pronounced population decline. The link between the number of population and the number of students in a region is, however, not very close due to the spatial mobility of students. Hence, competition for students between universities will play an increasing role.